(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the theoretical and practical foundations of integrating innovative pedagogical technologies into the process of teaching natural sciences in primary education. It analyzes the essence of innovative approaches, their advantages in the learning process, and their role in developing students’ scientific thinking, critical reasoning, and creativity. The paper presents effective ways of adapting technologies such as STEAM, project-based learning, ICT, digital platforms, and interactive methods to natural science lessons. In addition, the methodological conditions for implementing innovative technologies based on an integrated learning model, differentiated instruction, and a competence-based assessment system are scientifically justified. The practical section provides lesson design samples, recommendations for the application of innovative methods, and methodological guidelines for primary school teachers. Research findings demonstrate that innovative technologies enhance students’ interest in the subject, improve learning outcomes, and contribute to the formation of modern competencies.